Business Intelligence Applied : Implementing an Effective Information and Communications Technology Infrastructure - Gendron, Michael S., 1957- (Hoboken, New Jersey : WILEY, 2013)
BExpert guidance for building an information communication and technology infrastructure that provides best in business intelligence/b Enterprise performance management (EPM) technology has been rapidly advancing, especially in the areas of predictive analysis and cloud-based solutions. Business intelligence caught on as a concept in the business world as the business strategy application of data warehousing in the early 2000s. With the recent surge in interest in data analytics and big data, it has seen a renewed level of interest as the ability of a business to find the valuable data in a timely'and competitive'fashion. iBusiness Intelligence Applied/i reveals essential information for building an optimal and effective information and communication technology (ICT) infrastructure.ulliDefines ICT infrastructure/liliExamines best practices for documenting business change and for documenting technology recommendations/liliIncludes examples and cases from Europe and Asia/liliWritten for business intelligence staff, CIOs, CTOs, and technology managers/li/ul With examples and cases from Europe and Asia, iBusiness Intelligence Applied/i expertly covers business intelligence, a hot topic in business today as a key element to business and data analytics.
Foreword -- Preface -- Acknowledgments -- Introducing ICT strategy -- Defining information and communication technology infrastructure -- Introductory business and technology strategy concepts -- Why build ICT infrastructure to support business processes? -- Understanding how ICT produces value -- Understanding your organization and its competitive environment -- Process improvement or innovation? -- Measuring the business value of ICT -- Best practices for documenting process change -- Best practices for documenting technology recommendations -- The business-driven infrastructure design (BDID) cycle -- Appendix ticket sales, Inc.: a fictitious business case -- About the author -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business intelligence; BUSINESS & ECONOMICS -- Corporate Governance; BUSINESS & ECONOMICS -- Leadership; BUSINESS & ECONOMICS -- Organizational Development; BUSINESS & ECONOMICS -- Workplace Culture; Business intelligence; Business intelligence; Electronic books; Electronic books